Perceived movement skill competence in stability: Validity and reliability of a pictorial scale in early adolescents. (27th February 2021) - Estevan, Isaac; Menescardi, Cristina; Castillo, Isabel; Molina‐García, Javier; García‐Massó, Xavier; Barnett, Lisa M.
Abstract : Perceived motor competence (PMC) is important to health as it mediates the association between actual motor competence (AMC) and physical activity. Many instruments assess the broader construct of physical self‐perception but no scale has been developed to assess PMC in stability. The aim of this study was to develop and analyze the reliability and validity of a new pictorial PMC in stability skill assessment when completed by early adolescents. A Delphi method showed ≥70% of experts' consensus in the seven proposed items. A sample of 904 students (11‐14 years old) self‐reported PMC in locomotion, object control, and stability using two pictorial scales: Perceived Movement Skill Competence (PMSC) and the newly developed Stability (PMSC_Stability). The Körperkoordinations test for Kinder (KTK) was also administered as a measure of AMC in skills that utilize stability. Two different subsamples were randomly assigned to criterion validity and reliability assessments. Spearman's correlation, confirmatory factor analysis, and a general linear model for sex and age were conducted. The internal consistency (α) and test‐retest (intraclass correlation coefficient) reliability values were good (>0.70). A single‐factor latent model represented stability and did not differ by sex. Stability perception was associated with AMC (rho = 0.51). Stability is important to the performance of many movement skills (eg, single‐leg balance or moving on a narrow surface). Understanding which adolescents have poor stability perception could highlight stability as an area that needs targeting in order to increase physical activity and sport participation.